Interview with Dr. Marcelo Lopes de Souza: “Contemporary challenges offer Geography a unique opportunity to demonstrate its social relevance” - Huaytalla L., Victor A. (2020)
Marcelo Lopes de Souza is a Bachelor and Master in Geography from the Federal University of Rio de Janeiro. He completed his doctorate in Geography at the Universität Tübingen (Germany) and has been invited as a professor at different universities in Europe and Latin America. He is currently a tenured professor at the Federal University of Rio de Janeiro and coordinator of the Center for Research in Environmental Geography and Political Ecology (GAEP), linked to the Department of Geography of the same university. His academic interest focuses on the study of the links between social change and spatial organization. He is the author or organizer of seventeen books (thirteen published in Brazil, one in Germany, and three in England) and nearly one hundred and fifty articles and book chapters. In this interview, he shares his ideas about the social and political situation in Brazil in the face of the pandemic generated by COVID-19 and the contributions that geography should provide. In the same way, he exposes his thoughts about the development and evolution of the Brazilian geography. He also makes known his interest and academic production focused on Environmental Geography, Political Ecology, the relationship between space and nature from the libertarian perspective, social struggles, environmental justice as a dimension of socio-spatial development, among others. Finally, he concludes by highlighting the need for cooperation between geographers and social movements in the face of inequality and environmental injustice; not only participating as academic agents, but also through activism and the development of useful and collaborative knowledge.